Locke & key. [Vol. 5], Clockworks - Hill, Joe (Locke & Key, 2013)
The sprawling tale of the Locke family and their mastery of the "whispering steel" thunders to new heights as the true history of the family is revealed to Tyler and Kinsey. Zack Wells assumes a new form, Tyler and Kinsey travel through time, and surprises beyond imagination will be revealed before the sixth issue ends.